Trend analysis in the funding of university research in Nigeria: implications for social and economic development in an emerging economy (2012)
Adequate financing of university’s research is often believed to be one of the strong catalysts for successful economic development. However, in Nigeria, the problem of financing university’s research in particular and education in general is acute. This study, therefore, examined the trends in the financing of research in Nigeria’s publicly-owned federal universities. Secondary data obtained from various national statistical bulletins and other individual sources were used to answer the four research questions raised in the study. The results showed that research funding in Nigerian universities continuously witnessed a downward trend given the real Naira value over the years. Specifically, the study discovered that for a period of twenty years (1990-2009), the average research funds available to Nigeria’s federal universities was a dismal 1.3% of the total universities’ actual spending. Similarly, only 0.3% of the nation’s total GNP was spent on research in Nigeria as against 2.0% in South Korea; 3.0% in Japan and Germany; and 3.4% in the United States of America. The low investment in university-based research in Nigeria could have serious negative implication on the social and economic wellbeing of the country. In view of the imponderable benefits of university research, the study recommended that solid and deliberate effort be made by government towards improving financial investment in university research in the country